A comparative study on mental health outcomes in patients with rheumatoid arthritis and knee osteoarthritis - Meng Jia; Shuang Wang; Chenxi Yu; Ping Li (Frontiers in Medicine, 2026)
Objective This study aimed to analyze the current status and differences in mental health levels between patients with rheumatoid arthritis (RA) and knee osteoarthritis (OA) to provide a reference for clinical nursing interventions. Methods Using convenience sampling, patients with knee osteoarthritis and rheumatoid arthritis who were hospitalized at a tertiary first-class hospital in Shandong Province from May to August 2025 were selected for a cross-sectional survey, and the differences in mental health levels between the two groups were compared. Results There were significant differences between the OA and RA groups in the Symptom Checklist-90 (SCL-90). Except for terror, paranoia, and other dimensions, there were statistically significant differences in the scores for each SCL-90 dimension between the two groups ( p < 0.001). Conclusion In summary, RA patients exhibit lower psychological health levels than OA patients. In addition, there were differences in social demographic characteristics that affected the mental health of both groups. In clinical practice, healthcare professionals should focus on mental health of RA and OA patients, acknowledge the adverse consequences of psychological problems, and carry out targeted interventions to improve patients’ quality of life and their mental wellbeing.